Potential ways to address antimicrobial resistance across India and wider exacerbated by COVID-19 - Mainul Haque, Johanna C. Meyer, Brian Godman,, (Journal of Applied Pharmaceutical Science, 2021)
This article does not have an abstract.
Keywords: Antimicrobial resistance, AMR, COVID-19, India.